Quantum probability and infinite dimensional analysis: from foundations to applications - Schürmann, Michael; Franz, Uwe (World Scientific, 2005)
This volume collects research papers in quantum probability and related fields and reflects the recent developments in quantum probability ranging from the foundations to its applications
"Krupp-Kolleg Greifswald, Germany, 22-28 June 2003. - Papers collected from a school, three workshops and an international conference. - Includes bibliographical references. - Description based on print version record
Includes bibliographical references
Papers collected from a school, three workshops and an international conference
Keywords: Electronic books; Electronic books -- Conference proceedings; Konferenzschrift